Brain-acting hepatokines: its impact on energy balance and metabolism - Giovanini, Lucía; Wanionok, Nahuel; Perello, Mario; Cornejo, Maria Paula (Frontiers in Neuroscience, 2025)
The liver is recognized for its central role in energy metabolism, yet emerging evidence highlights its function as an endocrine organ, secreting a variety of proteins—hepatokines—that influence distant tissues. Hepatokines not only regulate metabolic processes by acting on peripheral tissues but also exert direct effects on brain function. In this mini-review, we discuss the existing literature on the role of “brain-acting” hepatokines including IGF-1, FGF21, LEAP2, GDF15, and ANGPTLs, and their impact on energy balance and metabolism. We review the existing evidence regarding their roles in metabolism through their action in the brain, and their potential implications in metabolic disturbances. By integrating insights from recent studies, we aim to provide a comprehensive understanding of how liver-derived signals can modulate energy balance and metabolism.